Lake Victoria Ecology, Resources, Environment - Awange, Joseph L.; Ong$1 (Bang$1 (Ba, Obiero.s; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Recently, there has been, and continues to be, a tremendous interest on Lake Victoria and its environs, both locally and internationally. A casual browsing on the Internet indicates that the entries on the Lake have been rising phenomenally. At the same time, the issues discussed are as diverse as they are varied in their treatment of the subject, both in terms of depth and comprehensiveness. The information on Lake Victoria and its environ is scattered, isolated, and sometimes confusing even though documentation on the subject are available. Despite this situation, the fact remains that various people (e. g. , secondary and universitystudents,researchers,practitioners,etc. ,)wouldliketoaccess and know more about the Lake and its environs. Aware of the existing information gap about this world$1 (Bs second largest fresh water Lake, this book is intended to provide readers with up-to-date information pertaining the Lake. The book gives an in-depth coverage of environmental issues, - source endowment, poverty amidst plenty, development opportunities, challenges and other related issues facing the Lake and its environs. It aims at providing information on the above variables, which hopefully will address the needs of various users. We have attempted to present the materials in a simple and straight forward way that will be und- standable to undergraduate students as well as advanced researchers. YetweareawarethatmostparametersoftheLakearechangingrapidly. We have therefore attempted to provide as accurate and up-to-date - formation up to the time of publishing.s
Background of Lake Victoria -- Resources -- Eco-Tourism -- Environmental Concerns and Management -- Poverty Challenges in the Lake Victoria Basin -- Economic Development -- Rich Wetlands of Lake Victoria -- Management of Lake Victoria -- Challenges Facing Lake Victoria -- Application of Satellites to Lake Victoria.
Keywords: Environment; Geobiology; Regional planning; Urban planning; Physical geography; Ecosystems; Environmental management; Ecotoxicology; Environment; Environmental Management; Ecotoxicology; Biogeosciences; Ecosystems; Physical Geography; Landscape/Regional and Urban Planning; Electronic books